2006
DOI: 10.1190/1.2353803
|View full text |Cite
|
Sign up to set email alerts
|

Theory of vibratory mobilization on nonwetting fluids entrapped in pore constrictions

Abstract: Quantitative dynamics of a nonwetting ganglion of residual oil entrapped in a pore constriction and subjected to vibrations of the pore wall can be approximated by the equation of motion of an oscillator moving under the effect of the external pressure gradient, inertial oscillatory force, and restoring capillary force. The solution of the equation provides the conditions under which the droplet experiences forced oscillations without being mobilized or is liberated from its entrapped configuration if the acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 15 publications
0
62
0
Order By: Relevance
“…[14] Dislodging particles and bubbles by fluid flow induced by time-varying stresses are mechanisms that depend on the frequency of deformation [e.g., Beresnev, 2006]. The pressure gradients created by inhomogeneous poroelastic properties will be proportional to strain amplitude.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Dislodging particles and bubbles by fluid flow induced by time-varying stresses are mechanisms that depend on the frequency of deformation [e.g., Beresnev, 2006]. The pressure gradients created by inhomogeneous poroelastic properties will be proportional to strain amplitude.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism or mechanisms responsible for mud volcano responses remain uncertain. Possible explanations include an increase in permeability or fluid mobility resulting from the mobilization of trapped colloidal particles [e.g., Roberts and Abdel-Fattah, 2009] or bubbles [e.g., Beresnev, 2006] by the time-varying flows produced by the passage of seismic waves.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent interest in using acoustic waves to enhance oil recovery has stimulated a significant amount of work on the interaction of acoustic waves with non-wetting oil blobs in porous media [127,128]. It has been found that acoustic waves may induce capillary resonance of the blobs and the size of the blob (L) can be related to the resonant frequency (ω) by [127]:…”
Section: Model Analysis: First Order Approximationmentioning
confidence: 99%
“…From subsequent experiments (Li et al (2005);Beresnev et al (2011)) and numerical simulations at pore scales (Beresnev (2006); Beresnev and Deng (2010); Deng and Cardenas (2013)), they concluded that the acceleration of the rock matrix should be in the order of 0.1 to 10m/s 2 , or more, to induce oil mobilization. They further showed that such a threshold acceleration level varies depending on a number of parameters: a) the average size of the pore space; b) the background pressure gradient; c) the wave frequency; d) the viscosity of the remaining oil; and e) the capillary pressure.…”
Section: Introductionmentioning
confidence: 94%
“…It has also been suggested that the movement of the pore walls could also mobilize oil droplets trapped in pore spaces (Averbakh et al (2000); Beckham et al (2010); Beresnev and Johnson (1994); Beresnev (2006); Hilpert et al (2000)). That is, the vibration of pore walls can dislodge the trapped droplets and coalesce them into larger ones, allowing them to be mobilized and flow, as illustrated in Figure 2.…”
Section: Introductionmentioning
confidence: 97%